“Beyond the Knife”—Applying Theranostic Technologies to Enhance Outcomes in Neurosurgical Oncology - Santosh Guru; Fred C. Lam; Amirhossein Akhavan-Sigari; Yusuke S. Hori; Deyaaldeen AbuReesh; Armine Tayag; Sara C. Emrich; Louisa Ustrzynski; David J. Park; Steven D. Chang (Brain Sciences)
The current standard of care for brain tumor management includes maximal safe surgical resection followed by concurrent chemotherapy and radiation therapy. Recent advances in image-guided surgical techniques have enhanced the precision of tumor resections, yet there remains a critical need for innovative technologies to further improve patient outcomes. Techniques such as fluorescence image-guided neurosurgery in combination with stereotactic radiosurgery have improved outcomes for patients with brain tumors. In this article for Brain Science’s Special Issue Recent Advances in Translational Neuro-Oncology, we review the use of image-guided neurosurgery and stereotactic radiosurgery for the treatment of brain tumors. In addition, we summarize the emerging use of theranostic nanoparticles for the delivery of diagnostic and therapeutic technologies to enable the neurosurgeon to perform more precise surgical resections in the operating room, to specifically target the delivery of existing and novel treatments to tumor cells, and to augment the efficacy of stereotactic radiosurgery. These innovative translational tools will allow neurosurgeons, neuro-oncologists, and radiation oncologists to go “beyond the knife” to improve the survival of brain tumor patients.